Evaluación de factibilidad técnica para una planta geotérmica en Paipa-Iza, Boyacá (2023)
The main objective of this research was based on the evaluation of technical feasibility for a geothermal plant in Paipa-Iza, Boyacá. Which, was divided into four objectives to solve; characterization of the geothermal fluid, design a clean steam generation system using heat from a geothermal reservoir, carry out the design of the steam turbine for electricity generation and finally determine the conditions for reinjection of the geothermal fluid into the reservoir to avoid degradation of the geothermal fluid. resource.